Comparison of the antiplatelet and antithrombotic effects of bivalirudin versus unfractionated heparin: A platelet substudy of the HEAT PPCI trial. Issue 172 (December 2018) - Khanna, Vikram; Shahzad, Adeel; Thayalasamy, Kala; Kemp, Ian; Mars, Christine; Cooper, Rob; Roome, Claire; Wilson, Keith; Harris, Scott; Stables, Rod; Curzen, Nick
Abstract: In randomised trials, bivalirudin has been associated with higher rates of acute stent thrombosis (AST) compared to unfractionated heparin (UFH), without mechanistic explanation. Furthermore, data are discrepant regards the antiplatelet effects of bivalirudin. This prespecified study, part of a larger HEAT-PPCI Platelet Substudy, aimed to compare the antiplatelet and antithrombotic effects of bivalirudin and UFH using short thrombelastography (s-TEG), an ex vivo whole blood platelet function assay. In HEAT-PPCI, patients were randomised to receive UFH or bivalirudin before angiography. Assay with s-TEG was performed in 184 patients (10.2%) at end of procedure (EOP) and repeated at 24 h. In addition to adenosine diphosphate- (ADP) and arachidonic acid- (AA) mediated platelet aggregation, thrombin-mediated clotting (TMC) was assessed using kaolin with and without heparinase. There were no significant differences between UFH and bivalirudin in ADP- and AA-mediated platelet aggregation at EOP or 24 h. Whilst UFH obliterated TMC at EOP, bivalirudin prolonged R time (19.7 min [15.9–25.4] vs. 8.4 min [7.5–10]; P < 0.0001), K time (2.4 min [1.9–3.4] vs. 2.2 min [1.8–2.7]; P = 0.007) and significantly increased maximum clot strength (MA 62.7 mm [58.7–67.4] vs. 58.6 [55–63]; P = 0.0005), compared to control. In conclusion, there were no significant differences in the antiplatelet effects of UFH and bivalirudin. However, whilst UFH obliterated TMC, bivalirudin prolonged clot initiation but potentiated maximum clot strength. As AST is likely multifactorial in aetiology, in patients treated with bivalirudin, increased clot strength may contribute to this hazard in some individuals and this observation warrants further investigation. Highlights: Comparing the antiplatelet and antithrombotic effects of bivalirudin and heparin No significant differences in the antiplatelet effects of bivalirudin and heparin Heparin totally obliterated thrombin-mediated clotting. Bivalirudin prolonged clot initiation/propagation and increased clot strength. Increased clot strength with bivalirudin may contribute to acute stent thrombosis.